2021
DOI: 10.1519/jsc.0000000000003341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Resistance Training and Weightlifting on Injury Risk Factors and Resistance Training Skill of Adolescent Males

Abstract: The purpose of this study was to investigate the effects of resistance training with or without weightlifting on risk factors for injury and resistance training skill in circa-peak height velocity boys. Sixty-seven boys (age 12-14 years) from a local secondary school were divided into three groups: combined resistance training (CRT), combined resistance training with weightlifting movements (CRT&WL), or a control group (CON). Experimental groups completed twiceweekly training programs over the course of an aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…The limited improvements in the TRT group may have also been responsible for the greater ES found in favour of WLT, however limited information on the TRT prescription employed in the study prevent any further exploration [40]. Pichardo et al [59] reported large ES for CMJ performance in favour of WLT in comparison with the other studies included in the meta-analysis. The training intervention duration employed in the study was 28 weeks [59], which may have resulted in more pronounced improvements in measures of power compared with the other studies included in the WLT versus TRT analysis that implemented shorter training durations (median training duration: 8 weeks, range 6-28) [90].…”
Section: Weightlifting Training Versus Traditional Resistance Trainingmentioning
confidence: 96%
See 3 more Smart Citations
“…The limited improvements in the TRT group may have also been responsible for the greater ES found in favour of WLT, however limited information on the TRT prescription employed in the study prevent any further exploration [40]. Pichardo et al [59] reported large ES for CMJ performance in favour of WLT in comparison with the other studies included in the meta-analysis. The training intervention duration employed in the study was 28 weeks [59], which may have resulted in more pronounced improvements in measures of power compared with the other studies included in the WLT versus TRT analysis that implemented shorter training durations (median training duration: 8 weeks, range 6-28) [90].…”
Section: Weightlifting Training Versus Traditional Resistance Trainingmentioning
confidence: 96%
“…Four studies included youth participants, with the term youth referring to the period of life before adulthood and including individuals under 18 years of age [66]. Of these studies, only one included information on participants' stage of maturation [59], using the maturity offset method to estimate maturity status [67]. The majority of studies were conducted with solely male participants (n = 12), with three of the studies including both male and female participants, and one study with female participants only.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, young individuals have been reported to be particularly susceptible to injuries before and during the growth spurt (61) and careful prescription of a training program (i.e., training mode and characteristics) is especially important during these periods to prevent injuries that may limit future potential. The findings of recent research can offer some guidelines on a training program that may be used to effectively improve performance, while likely minimizing injury risk during this period (46,47). The complexities of training/match load management in the growing and maturing child to promote training adaptations and subsequent athletic performance, combined with the susceptibility to acute and chronic injuries are often not taken into account in LTAD models that promote sensitive periods.…”
Section: Characteristics Of the Training Methods During The Sensitive Periodsmentioning
confidence: 99%